KAJIAN POLA PEMANFAATAN RUANG DI KABUPATEN GARUT BERBASIS DAYA DUKUNG LINGKUNGAN HIDUP - Ardhy Firdian; Baba Barus; Didit Okta Pribadi (Jurnal Ilmu Tanah dan Lingkungan, 2010)
Enviromental carrying capacity was measured in three methods,i.e land capability, land carrying capacity and water carrying capacity. Garut Regency which is located at the upstream Cimanuk Watershed has an important role in the sustainability of capacity for downstream area. The aims of this study are: (1) to identify land use in Garut Regency in 2009, (2) to identify land capability in Garut Regency, (3) to assess the suitability of land use with land capability and space pattern in Garut Regency, (4) to identify the status of environmental carrying capacity in Garut Regency, and (5) to set a space pattern based on environmental carrying capacity. Based on the interpretation of Landsat Satellite Imagery in 2009, dryland agriculture has dominated the coverage about 45.4% and forest cover about 23.8%. This study also shows that most area in Garut Regency is belong to Class IV land capability (36.4% of the regency area) without Class I of land capability. Suitabilty evaluation between land cover and land capabilty describe that 48,45% area is suitable, 50.4% area is not suitable and 1.18% area is conditionally suitable depending on limitation factors that affect land capability. Another evaluation between space patern and land capability shown that 59.0% area is suitable, 32.1% area is not suitable, and 8.84% area is conditionally suitable. Both status of land carrying capacity and water carrying capacity are deficit. According to spatial pattern based on land capability and existing forest, space that can be use as the preservation area is about 58.5% of the area, and space that can be use as the cultivation area is about 41.5% of the area of Garut Regency.Keywords : Land capability, land cover/use, spatial pattern, water carrying capacity